Abundance and habitat associations of two Florida crayfishes, Procambarus paeninsulanus (Faxon, 1914) and P. fallax (Hagen, 1870) (Decapoda: Astacoidea), assessed with N-mixture modeling. Issue 3 (29th March 2018) - Manteuffel-Ross, Tiffani M; Stolen, Eric; Hinkle, C Ross
Abstract: The study of crayfishes in their native habitats is limited, even if crayfishes are economically and ecologically important. Such is the case in southeastern USA, a center of global crayfish diversity. This study investigated model-estimated abundance and habitat associations of Procambarus paeninsulanus (Faxon, 1914) and P. fallax (Hagen, 1870) in two spring-fed rivers, Wakulla and Silver rivers, in northwestern Florida. N-mixture models, a class of hierarchical models that account for detectability, were used to estimate abundance and detection probability. We also compared abundance to mean catch per unit effort (CPUE). Model selection assessed the relative evidence of hypotheses that related habitat covariates to crayfish abundance. We used baited minnow traps over four seasonal sampling surveys in one year. We caught 1, 257 specimens of P. paeninsulanus and 268 of P. fallax . Depending on the survey, males were 56–74% of the total. The abundance of P. paeninsulanus was predicted by dissolved oxygen, dominant vegetation or bottom type, and season; abundance estimates (with 95% confidence intervals) ranged from 3.9 (2.3–6.6) to 18.5 (2.0–157.5) per site, while mean CPUE (± standard deviation) ranged from 0 (± 0) to 6 (± 0.8) per 48 h of trap time per site. The abundance of P. fallax was predicted by percent coverage of vegetation and the null model; abundance estimates (with 95% confidence intervals) ranged from 10.3 (1.7–54.9) to 20.8 (2.2–119.7) per site, while mean CPUE (± standard deviation) ranged from 0 (± 0) to 3.3 (± 2.4) per 48 h of trap time per site. Results will assist managers in population monitoring in areas where these species may be impacted by herbicidal treatment of invasive plants. This study fills knowledge gaps on the ecology of Florida crayfishes by providing data on habitat association and relative abundance, information which is valuable to conservation and management efforts.